Atuação do profissional de educação física e o cuidado de si na atenção primária à saúde: processos e construções - Rodrigues, José Damião (2021)
In any field of activity, it is necessary to have general and specific knowledge related to the good development of professional performance. Thus, we aim to analyze the perception and knowledge of physical education professionals (PEP) working in the Expanded Nucleus of Family Health and Basic Care (Portuguese acronym: NASF-AB), concerning the care of themselves and others in the processes and constructions of this field of action. The research is characterized as qualitative in nature, carried out through an audio-recorded interview. The sample consisted of 14 PEP workers from the NASF-AB in the city of João Pessoa-PB. For data collection, a semi-structured interview script and audio recorder were used, and, for data analysis the Bardin content analysis technique was used. Ethical precepts were strictly respected. The results indicate knowledge of the PEP regarding the current guidelines and ordinances of the Ministry of Health, however, their greatest difficulty is to manage the basic family health unit concurrently with its core activity, as it makes self-care more difficult. In addition, the PEP identify care as broad and complex; they know about taking care of themselves and see the need to take care of themselves so they can take care of others; maintain a good bond with users; they do not perform matrix support; they do not carry out popular health education; and there is little knowledge on the subject, with an understanding that is still confused. We concluded that, despite the difficulties faced by the PEP, such as inadequate training, lack of equipment, reference and counter-referral, among others, from their lived experiences, they acquired knowledge with the praxis, but still insufficient to promote self-care integral, which involves the full understanding of the subject. Even though they have competences for their actions in health, they are currently plastered by the political system, which prevents them from acting in accordance with the guidelines and notebooks of the primary health care. In the field of health, self-care stands out and is something much broader and more complex than clinical practice. It’s necessary that the core of physical education transcends the biological aspects of assessment and exercise prescription, as care should to be carried out holistically and seen with a view that takes into account the human being, his subjectivity, his self-governance and his role in the construction of his story, which still seems far from reality.